Efecto de la fertilización mineral en diferentes momentos de aplicación sobre la floración y producción de Rubus glaucus Benth, en la parroquia Imbana - Asanza Espinoza, Karla Jazmín (2020)
Lastly, the demand for blackberry (Rubus glaucus) has increased due to its social importance and nutritional potential. In Ecuador, the yield is below the world average; mainly, due to poor agronomic management, lack of basic technical information, ambiguity about integral fertilization and its relationship to phenology. Therefore, the need arises to evaluate these effects and how they influence the production and quality of the fruit. In order to determine the effects of mineral fertilization, with macro and micro elements applied at different phenological moments such as pre-flowering, flowering and post-fruit setting on the blackberry quality and production parameters. A field trial was carried out in the Imbana parish, province of Zamora Chinchipe, for a period of 5 months under a completely randomized design with seven treatments: 1 (N, P, K applied in 3MF), 2 (N, P, K applied in 2MF), 3 (Ca, Mg, Zn, B, S, N, P, K applied in 3MF), 4 (Ca, Mg, Zn, B, S applied in 2MF), 5 (N, P, K, Ca, Mg, Zn, B, S applied in 3MF), 6 (N, P, K, Ca, Mg, Zn, B, S applied in 2MF) and control, with four repetitions. Variables were evaluated at the morphological, physiological, productive and quality levels. The results indicate that the fertilization with Ca, Mg, Zn, B, S supplied in pre-flowering and post-setting increased the weight of the fruits, aimed at fruits with 5.19 g as well as improved the diameter (25.13 mm) and length (18.26 mm), which translates into large caliber fruits, according to INEN 2427. While, for the productive and quality parameters of the fruit, no significant differences were evidenced, therefore, there is no clear effect of the fractionated mineral fertilization in two or three moments on these parameters for these growing conditions. Keywords: fertilization, blackberry, phenology, nutrients